The Effect of eWOM on Movie Sales Considering Competition and Culture - Lee, JungWon; Park, Cheol (Asia Marketing Journal (Online), 2024)
This paper aims to empirically analyze how competitive and cultural factors moderate the relationship between electronic word-of-mouth (eWOM) characteristics and sales in the US and Korean film industries. A conceptual model was developed based on the cue utilization theory (CUT) to analyze the role of cultural and competitive factors that moderate the relationship between three characteristics of eWOM (volume, valence, and variance) and movie sales. Data of 45 days of 163 films released in Korea and the US were collected and a total of 7,335 samples were analyzed by panel regression. As results, competitive factors enhanced the influence of the eWOM of a focal film and this moderating effect depended on the eWOM characteristics. It also revealed that the effect of eWOM had a greater effect on movie sales in Korea than in the US.